Financial Literacy and Financial Wellbeing - Empirical Evidence from Recent Graduates in Jaffna - Mithila, G.; Kabishka, T. (University of Ruhuna, 2025)
Financial literacy and financial well-being are crucial aspects of individuals' economic empowerment and overall quality of life. The study aims to investigate the impact of financial literacy and its dimensions, namely financial knowledge, financial behaviour, and financial attitude, on financial well-being among recent graduates in the Jaffna district. In addition, the study examines whether there is a difference in financial literacy levels between graduates who have received personal financial education and those who have not. Stratified sampling was used to select the sample, and over 200 questionnaires were distributed via social media, resulting in 125 respondents. Utilizing correlation analysis and multiple regression analysis with SPSS, the study found a significant positive relationship between overall financial literacy and financial well-being. Additionally, financial knowledge, behaviour, and attitude each demonstrated a significant positive impact on financial well-being. Further, the research revealed that graduates lacking personal financial education exhibit lower financial literacy levels than their counterparts with such education. These findings underscore the importance of integrating personal finance courses into educational curricula to enhance financial literacy and well-being among graduates.
Keywords: Behavioural economics; Financial attitude; Financial behaviour; Financial knowledge; Financial literacy; Financial well-being